Prevalence of asymptomatic SARS‐CoV‐2 infection in elective surgical patients in Australia: a prospective surveillance study. Issue 1 (9th January 2021) - Coatsworth, Nicholas; Myles, Paul S.; Mann, Graham J.; Cockburn, Ian A.; Forbes, Andrew B.; Gardiner, Elizabeth E.; Lum, Gary; Cheng, Allen C.; Gruen, Russell L.; ,
Abstract: Background: The study aimed to estimate the prevalence of active or previous SARS‐CoV‐2 infection in asymptomatic adults admitted for elective surgery in Australian hospitals. This surveillance activity was established as part of the National Pandemic Health Intelligence Plan. Methods: Participants ( n = 3037) were recruited from 11 public and private hospitals in four states (NSW, Vic, SA and WA) between 2 June and 17 July 2020, with an overall 66% participation rate. Presence of SARS‐CoV‐2 viral RNA was assessed by Reverse Transcriptase ‐ Polymerase Chain Reaction (RT‐PCR) analysis of nasopharyngeal swabs taken after induction of anaesthesia. Presence of anti‐SARS‐CoV‐2 antibodies was assessed by analysis of serum collected at the same time using a novel dual‐antigen ELISA assay. Results: No patient (0/3010) returned a positive RT‐PCR result. The Bayesian estimated prevalence of active infection of 0.02% (95% probability interval 0.00–0.11%), with the upper endpoint being 1 in 918. Positive serology (IgG) was observed in 15 of 2991 patients, with a strong positive in five of those individuals (Bayesian estimated seroprevalence 0.16%; 95% probability interval 0.00–0.47%). Conclusion: These results confirm that during periods of low community prevalence of SARS‐CoV‐2 elective surgery patients without fever or respiratory symptoms had a very low prevalence of active SARS‐CoV‐2 infection. Abstract : During the COVID 19 pandemic decisions regarding elective surgery cessation had significant impact on patients and practitioners. This study formed part of the National Pandemic Health Intelligence Plan, and finds that in areas where community transmission of SARS Cov‐2 is low, the risk of an asymptomatic patient undergoing elective surgery having SARS CoV‐2 is very low.